Analisis Ekspor Minyak Kelapa Sawit (CPO) Indonesia - Abidin, Zainal (Jurnal Aplikasi Manajemen, 2008)
This research aim to analysis factors having an effect on to palm oil exporting (CPO) Indonesia, constraints that happened in export activity and strategy in increase exporting. Data collecting obtained from BPS, on duty Plantation and Bank Indonesia (BI) Year 1996-2005. Analysis model used model equation of square least stage two method simultaneous (2SLS) and descriptive analysis for the constraints of that happened and know strategy in make-up of exporting (CPO) Indonesia. Variable remain to : exporting volume Variable change: price, exchange rate, growth of production. Result of this research can be concluded that domestic palm oil price (CPO), International palm oil price (CPO), exchange rate and palm oil price by simultaneous have an effect on reality to palm oil exporting (CPO) Indonesia, while rupiah exchange rate by parsial do not have an effect on reality to exporting of palm oil (CPO) Indonesia. Strategy increase of palm oil exporting (CPO) Indonesia more instructed and improved in its development which have walked from annually and also more paying attention is rival and or period to come challenges and also pay attention international price, domestic price, exchange rate in determining policy in the effort increasing of palm oil exporting (CPO) Indonesia.